Desain Literasi Budaya dalam Pembelajaran Bahasa Indonesia di Perguruan Tinggi - Helaluddin, Helaluddin (ESTETIK : Jurnal Bahasa Indonesia, 2018)
The cultural literacy program is one of the six basic literacies proclaimed by the World Economic Forum in 2015. Foundational literacies are literacy, numeracy, scientific literacy, ICT literacy, financial literacy, and cultural and civic literacy. Cultural literacy is someone’s ability in understanding his culture and how to behave towards his culture as his nation’s identity. In other words, cultural literacy is the knowledge, perspectives, and contributions of a set of cultures that will be used by the learners in the process of reading and writing. This paper highlights the advantages of cultural literacy for university students. In addition, this paper also elaborates the teaching scenario of cultural literacy in Indonesian language course. Keywords: literacy, cultural literacy, Indonesian language course